Uso de resíduos da filetagem de jundiá (Rhamdia quelen) e ácido fítico para elaboração e conservação de embutido cárneo - Moura, Luciane Ferreira de (2012)
The industrial processing of fish fillets generates large amount of waste that can cause serious environmental problems due to improper disposal. However, after filleting, muscles of good quality are found in the carcass, which can be used for human consumption. An alternative is the production of mechanically separated meat (MSM) or mincend fish for use in the processing ham-like products. In this context, in order to facilitate the use of co-products from fish industry, and increase the nutritional value of processed products, a ham-like product was prepared with different levels of mincend catfish (Rhamdia quelen). However, as the MSM of fish is highly perishable, it was first studied the antioxidant activit of different concentrations of phytic acid on fish mincend and fillets. Concentrations of 0,025% and 0,05% of phytic acid were tested, comparing them to the effect of 0,05% sodium erythorbate. Results demonstrate better antioxidant potential of phytic acid in a concentration of 0,05%. Having defined this concentration, hams were prepared with levels of 25, 50 and 75% minced catfish treated with 0,05% phytic acid in order to evaluate the effect of adding different amounts of mincend fish treated with natural antioxidant attributes on chemical composition, color and instrumental texture as well as sensory characteristics in ham-like products, was elaborated based hams with levels 25, 50 and 75% mincend catfish treated with 0,05% phytic acid. Adding minced fish in different concentrations to hams preparation influenced on the centesimal composition of each formulation. Moisture content was significantly affected. The 25% minced fish formulation was the only one which did not differ from the control. Moisture decreased as minced fish content increased. Regarding ash, the formulation containing 50% minced fish was the only one which showed significant difference while the control did not differ from the ones containing minced fish. Protein levels did not differ significantly among formulations. With exception of the formulation with 50% mincend of red color intensity decreased with increasing content of mincend. The lightness was not significantly different at the end of the period in all formulations and yellow color after sixty days, the formulations with the addition of mincend had higher intensity as the content. Texture analysis showed significant difference among formulations only for the variable thoughness, showing that by increasing the amount of minced fish content, the product becomes less tough. Sensory analysis did not show significant difference for variables of color and appearance. As to color, the increase of minced fish content decreased preference. The most accepted flavor was the control formulation. All formulations showed significant difference in texture. For a purchase attitude, the best values were attributed to the control formulation. Prices decreased according to the increase of minced fish content. The final product oxidation and pH were assessed for sixty days and showed that the use of phytic acid in ham-like cooked products is more efficient than sodium erythorbate. Based on these results, it is concluded that producing ham by replacing part of pork meat with minced fish containing phytic acid is viable because it presents characteristics for human consumption.